HUMAN CATHELICIDIN ANTIMICROBIAL PEPTIDE LL-37 AS AN ANTIBACTERIA, ANTIFUNGAL, ANTIVIRAL AND WOUND HEALING AGENT - DEA DIAN NURHIKMAH; Insan Sunan Kurniawan Syah (Fakultas Farmasi, Universitas Padjadjaran, 2018)
LL-37 is a cathelicidin-derived peptide in human. This protein contains two helical regions, an unstructured C-terminal tail and a cathionic amphiphatic charge. This review described the functions of human cathelicidin antimicrobial peptide LL-37. Cathelicidin peptides were shown to have some functions like to kill bacteria by distrupting the bacterial membranes of Staphylococcus aureus, Micrococcus luteus and Salmonella gastroenteritis, fungicidal against Candida albicans and Aspergillus sp , and work as antiviral agent against vaccinia virus by direct disruptive action on the viral envelope. Besides its antimicrobial effects, cathelicidins also play a role in wound healing through direct interaction or stimulation of the immune system, stimulating angiogenesis and re-epitheliazation. From the studies, it showed that LL-37 is a potential protein for the development of new drugs in the future.